PENGEMBANGAN MEDIA ARTICULATE STORYLINE BERBASIS CTL PADA MATA PELAJARAN IPA DI SEKOLAH DASAR - Putri, Ditta Delfiana; Usman, Herlina; Wardhani, Prayuningtyas Angger (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to develop articulate storyline learning media based on contextual teaching and learning in science subjects in elementary schools. The method used in this research is the Research and Development method with the ADDIE model (Analyz, Design, Development, Implementation, Evaluation). This research is an analysis of the needs for articulate storyline learning media based on contextual teaching and learning with the research subjects being teachers and fifth grade elementary school students. The data collection instruments used were questionnaires and interviews. The results of this research show that 60% of students need interesting learning media, 50% of learning with image-dominated media helps students understand material about the earth and 60% of students need learning media that can be taken anywhere. Students consider that material about the earth with the theme Let's Get to Know Our Earth in science lessons is quite difficult material and requires learning methods and teaching aids that can help students understand the material. Interview results from teachers stated that there were obstacles in teaching because they still used simple media and conventional teaching methods. By using an articulate storyline based on contextual teaching and learning, it is hoped that students will be motivated to learn according to the results of the needs analysis related to the media developed for students in elementary schools.